2008
DOI: 10.1261/rna.748408
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TTP mRNA targets in human dendritic cells reveals TTP as a critical regulator of dendritic cell maturation

Abstract: Dendritic cells provide a critical link between innate and adaptive immunity and are essential to prime a naive T-cell response. The transition from immature dendritic cells to mature dendritic cells involves numerous changes in gene expression; however, the role of post-transcriptional changes in this process has been largely ignored. Tristetraprolin is an AU-rich element mRNAbinding protein that has been shown to regulate the stability of a number of cytokines and chemokines of mRNAs. Using TTP immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 66 publications
2
64
0
Order By: Relevance
“…The MEK/ERK pathway stabilizes dusp6 mRNA These changes in the amounts of dusp6 mRNA could reflect a modification of dusp6 transcription, as documented in Ekerot et al (2008) but also changes in dusp6 mRNA stability, as described previously for dusp1 (Lin et al, 2007;Emmons et al, 2008;Kuwano et al, 2008). Time-course experiments of either LS174, A375, or the non-transformed HEK293 cells with the transcription inhibitor DRB (5,6-dichloro-1-beta-Dribofuranosylbenzimidazole) have allowed determining that dusp6 mRNA has a short half-life ranging from 20 to 40 min according to the cell type ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…The MEK/ERK pathway stabilizes dusp6 mRNA These changes in the amounts of dusp6 mRNA could reflect a modification of dusp6 transcription, as documented in Ekerot et al (2008) but also changes in dusp6 mRNA stability, as described previously for dusp1 (Lin et al, 2007;Emmons et al, 2008;Kuwano et al, 2008). Time-course experiments of either LS174, A375, or the non-transformed HEK293 cells with the transcription inhibitor DRB (5,6-dichloro-1-beta-Dribofuranosylbenzimidazole) have allowed determining that dusp6 mRNA has a short half-life ranging from 20 to 40 min according to the cell type ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…TTP is an important regulator of the decay of a subset of ARE-containing mRNAs (17,21,34,48,56,58). However, since multiple cellular AUBPs other than TTP can recognize the ARE sequence and exert synergistic or opposing effects (40,68), it can be difficult to discern the exact role of TTP in the context of the ARE in cells.…”
Section: Resultsmentioning
confidence: 99%
“…To date we cannot completely exclude that TTP triggers the activation or repression of other ARE-binding proteins through protein-protein interactions or that the loss of function mutation in the zincfinger concerns only a subset of ARE-containing targets. In this regard, a recent finding revealed that TTP does not exclusively bind to ARE sequences, but additionally recognizes a non-ARE cis element in the major histocompatibility complex class I mRNA (53). However, 3Ј-untranslated region analysis of this mRNA demonstrated a binding deficiency of the zinc-finger mutant as well, suggesting that the loss of function is not restricted to a certain ARE motif.…”
Section: Genementioning
confidence: 96%